2011
DOI: 10.1074/jbc.m111.264788
|View full text |Cite
|
Sign up to set email alerts
|

External Ba2+ Block of the Two-pore Domain Potassium Channel TREK-1 Defines Conformational Transition in Its Selectivity Filter

Abstract: TREK-1 is a member of the two-pore domain potassium channel family that is known as a leak channel and plays a key role in many physiological and pathological processes. The conformational transition of the selectivity filter is considered as an effective strategy for potassium channels to control the course of potassium efflux. It is well known that TREK-1 is regulated by a large volume of extracellular and intracellular signals. However, until now, little was known about the selectivity filter gating mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 43 publications
5
47
1
Order By: Relevance
“…The alternative translation initiation codon is 42 amino acids upstream from the first methionine in the sequence at the N-terminus of the channel. The N-terminus truncated form gives rise to a current with a much reduced open probability and a collapsed selectivity filter with both a reduced potassium selectivity [61,74,94,100] and a measurable permeability to sodium [94]. Treatment with both DEPC and fenamates, substantially enhances current through the Nterminus truncated form of the channel, and, interestingly, measurements of the reversal potential in the presence of these compounds reveal that the enhanced currents have become highly K selective [99,100].…”
Section: Fenamatesmentioning
confidence: 94%
“…The alternative translation initiation codon is 42 amino acids upstream from the first methionine in the sequence at the N-terminus of the channel. The N-terminus truncated form gives rise to a current with a much reduced open probability and a collapsed selectivity filter with both a reduced potassium selectivity [61,74,94,100] and a measurable permeability to sodium [94]. Treatment with both DEPC and fenamates, substantially enhances current through the Nterminus truncated form of the channel, and, interestingly, measurements of the reversal potential in the presence of these compounds reveal that the enhanced currents have become highly K selective [99,100].…”
Section: Fenamatesmentioning
confidence: 94%
“…Thomas et al (2008) describe the N terminus truncated form of TREK1 (TREK1DN) as being regionally and developmentally regulated in a number of different regions of the rat central nervous system. Both forms are expressed in COS-7 cells (Thomas et al, 2008) but predominantly the long form is found in human embryonic kidney 293 cells (Ma et al, 2011). For the related K2P channel TREK2, which also undergoes ATI (Simkin et al, 2008), the degree of ATI has been shown to be tissue specific (Staudacher et al, 2011) through differential regulation of mRNA translation.…”
Section: N Terminus Modulates Trek1 Channel Pharmacologymentioning
confidence: 99%
“…TREK1DN has been described as a constitutively "nonconductive" variant, with a "collapsed selectivity filter" (Ma et al, 2011) that is permeable to sodium under normal physiologic conditions, leading to membrane depolarization when it is active in neurons (Thomas et al, 2008). Furthermore, TREK1DN has been shown to copurify with the longer form (Thomas et al, 2008), so heteromers may also exist.…”
Section: N Terminus Modulates Trek1 Channel Pharmacologymentioning
confidence: 99%
“…[5]. However, we have very limited information about its possible effect on background leak channels [26], or on cardiac Ca 2+ activated K + channels. Therefore, we should not assign the significant Ca 2+ sensitivity of I K1 to a single channel type.…”
Section: Multifactor Regulation Of I K1 ?mentioning
confidence: 99%